2017
DOI: 10.1002/esp.4107
|View full text |Cite
|
Sign up to set email alerts
|

Total organic carbon fluxes of the Red River system (Vietnam)

Abstract: Riverine transport of organic carbon from terrestrial ecosystems to the oceans plays an important role in the global carbon cycle. The Red River is located in Southeast Asia where river discharge, sediment loads and fluxes of elements (carbon, nitrogen and phosphorus) associated with suspended solids have been dramatically altered over past decades as a result of reservoir impoundment and land use, population, and climate change. Dissolved organic carbon (DOC) and particulate organic carbon (POC) concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Our estimation is similar to the measured result. Another example, the reported annual POC fluxes in the Hong River (Red R.) and Brantas River are 0.15 and 0.015 Mt C, respectively [ Le et al ., ; Jennerjahn et al ., ], but the estimated values are 0.92 ± 0.98 and 0.07 ± 0.07 Mt C, respectively. These significant differences resulted from differences in the sediment loads.…”
Section: Resultsmentioning
confidence: 99%
“…Our estimation is similar to the measured result. Another example, the reported annual POC fluxes in the Hong River (Red R.) and Brantas River are 0.15 and 0.015 Mt C, respectively [ Le et al ., ; Jennerjahn et al ., ], but the estimated values are 0.92 ± 0.98 and 0.07 ± 0.07 Mt C, respectively. These significant differences resulted from differences in the sediment loads.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies examining POM dynamics across discharge regimes have identified phytoplankton and degraded terrestrial detritus as important POM sources during low flows (including nonevent baseflows; Bukaveckas et al, 2011;Coynel et al, 2005;Dodds et al, 2004;Hatten et al, 2012;Le et al, 2017;Pettine et al, 1998;Relexans et al, 1988). These materials are typically characterized by elevated C and N contents and low C:N values (Meybeck, 1982).…”
Section: Contributions From Unidentified Sources During Low Event Flomentioning
confidence: 99%
“…Therefore, high erosion plus the character of soil types colour the water of the Thao River and the Da River into "red" [50]. In Vietnam, the same Acrisols dominate on the slopes, and grey or alluvial soils dominate in the valleys [41]. Land use in China is mainly forest, accounting for 62% of the area, followed by grassland and cultivated land, accounting for 19% and 18%, respectively [1] .…”
Section: General Characteristicsmentioning
confidence: 99%
“…The Red River is a typical Asian river system, combining different land uses, affected by human activities such as intensive dam implementations and agriculture [36,37]. Recent studies of hydrology and suspended sediment in this basin mainly used data from gauge stations or sampling to do statistical analysis [38][39][40][41], or use modeling to perform simulations at a local scale [42] or in the delta part [43] at a monthly scale; few studies analyzed fluxes at daily scale, but only on a short period [37], in the delta [44] or only for discharge or suspended sediment [45]. Both Q and SSC can vary greatly from day to day; therefore, it would be more favourable to calculate flux at a daily scale.…”
Section: Introductionmentioning
confidence: 99%